Peran Teknologi Informasi di Era Society 5.0 di Lingkungan Mesjid Jabal Nur SPN Padang Besi Kota Padang - Aisyah, Hesty; Sirait, Weri; Firdian, Fadil; Azizah, Nur; Andesti, Cyntia Lasmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The development of information system technology is growing rapidly so that it has an impact on trends that have emerged from the industrial revolution 4.0 and society 5.0. Higher education, one of which is an organization that contributes to educational activities in Indonesia, must be able to adapt to a number of emerging trends, including the trend of Society 5.0. Education which has also penetrated into the Jabal Nur Mosque environment in Padang City SPN needs to understand the roles and strategies that need to be assisted by the Higher Education in dealing with the era of society 5.0, by providing studies on the concepts and processes of society 5.0. From the results of observations and activities, it is obtained strategies that can be implemented by tertiary institutions, especially by increasing productivity through good cooperation between academics and mosque environmental parties to be able to support the role of information technology development through information technology management skills training for participants who are students within the Jabal Mosque environment Nur Padang City